Effect of Ethylmethacrylate and Isobutylmethacrylate on Surface Hardness and Surface Roughness of Heat-Cure Ocular Acrylic Resins - Hiba Munaf Hadi; Ayad I. Haddad; Firas Abd kati (Journal of Techniques)
Background Acrylic resin is a commonly utilized material in clinical practice, including:  maxillofacial prosthesis Interim prostheses, repair dentures, reline, orthodontic equipment, and record bases are only a few examples of possible applications. However, these materials have some drawbacks, for example low mechanical properties. To improve the performance of the acrylic resins, various materials have been incorporated.